Financial liberalization and long-run stability of money demand in Nigeria - Oludele E. Folarin; Simplice Asongu (African Governance and Development Institute (AGDI), 2017)
A stable money demand function is essential when using monetary aggregate as a monetary policy. Thus, there is need to examine the stability of the money demand function in Nigeria after the deregulation of the financial sector. To achieve this, the study employed CUSUM (cumulative sum) and CUSUMSQ (CUSUM squared) tests after using autoregressive distributive lag bounds test to determine the existence of a long run relationship between monetary aggregate and its determinant. Results of the study show that a long-run relationship holds and that the demand for money is stable in Nigeria. In addition, the inflation rate is found to be a better proxy for an opportunity variable when compared to interest rate. The main implication of the study is that interest rate is ineffective as a monetary policy instrument in Nigeria.
Keywords: E41; C22; 330; Stable; demand for money; bounds test